Pembuatan Deterjen Ramah Lingkungan Dari Buah Lerak - Rani Pramudyo Ningtyas; Lia Muliati; Rini Siskayanti; Alfi Aulia Ajilan; Rifa Mar’atul Fikriyah; Galu Murdikaningrum; Dini Yulilanti; Ilham Eka Santang (LPPM POLITEKNIK LP3I, 2024)
Detergents are the most polluting household waste because contain sulfonic surfactants, which are unbiodegradable, so there is a need to innovate environmentally friendly cleaning products. Household waste has become a serious global problem. However, the environmental impact of household waste is in the form of detergent waste, where the use of detergent sometimes exceeds the dosage and causes much more foam. Lerak fruit is a natural ingredient used as a raw material for the detergent. This community service aims to educate people on making environmentally friendly detergent which was held at the Sumedang Logistics Vocational School. This PKM activity was carried out by outreach to 25 teacher and student representatives. The main objective of this community service activity is to provide knowledge and training on environmentally friendly Lerak detergent to encourage the entrepreneurial spirit and skills of teachers and students of the Sumedang Logistics Vocational School. This activity is a real contribution to utilizing natural resources while maintaining environmental health. The detergent manufacturing process involves saponin extraction using a hot water extraction method, followed by formulation using additional ingredients such as organic fragrances.